INNOVATIVE SOLUTIONS TO ENHANCE RELIABILITY OF OIL & GAS PIPELINES AND TECHNICAL SAFETY IN TRANSPORT SYSTEMS - Tarakhtieva Gulmira Kulbaevna (Modern American Journals, 2025)
This article examines innovative engineering, organizational, and digital solutions that improve reliability and technical safety in oil and gas pipeline transport systems. The study integrates 2020–2024 evidence on integrity management, in-line inspection (ILI) performance, predictive maintenance, leak detection, and cyber-physical security to quantify economic and safety impacts. A mixed-methods design combines statistical comparison, cost–benefit analysis, and risk-based models calibrated to operator-reported indicators (incidents per 1,000 km, corrosion anomaly density, mean time to failure). Results indicate that integrating probabilistic integrity assessment, fiber-optic distributed sensing, advanced ILI analytics, and risk-based operations yields measurable reductions in failure probability and life-cycle cost. Policy and management implications are discussed with alignment to API/ASME/ISO standards and international practice.